2015
DOI: 10.1111/bjh.13544
|View full text |Cite
|
Sign up to set email alerts
|

Small nucleolar RNA expression profiles refine the prognostic impact of IGHV mutational status on treatment‐free survival in chronic lymphocytic leukaemia

Abstract: . (2011) The lymph node microenvironment promotes B-cell receptor signaling, NF-kappaB activation, and tumor proliferation in chronic lymphocytic leukemia. Blood, 117, 563-574. Hofbauer, S.W., Pinon, J.D., Brachtl, G., Haginger, L., Wang, W., Johrer, K., Tinhofer, I., Hartmann, T.N. & Greil, R. (2010) Small nucleolar RNA expression profiles refine the prognostic impact of IGHV mutational status on treatment-free survival in chronic lymphocytic leukaemiaChronic B-cell lymphocytic leukaemia (CLL) is generally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 9 publications
0
16
0
1
Order By: Relevance
“…Moreover, Valleron et al found that the overexpression of snoRNA HBI-239 and HBI-239-processed miRNA predicted good prognosis in angio-immunoblastic T-cell lymphoma (AITL) and PTCL not otherwise specified (PTCL-NOS) (86). Berquet et al investigated the snoRNA expression profiles in B-cell chronic lymphocytic leukemia (CLL) patients and identified that immunoglobulin heavy chain variable region gene (IGHV)-mutant patients exhibiting overexpression of 20 snoRNAs had a shorter treatment-free survival (TFS) (87). SNORA70F and SNORD116-118 were developed into a 2-snoRNA model that appeared to distinguish two different prognostic CLL groups (88).…”
Section: The Functions Of Snornasmentioning
confidence: 99%
“…Moreover, Valleron et al found that the overexpression of snoRNA HBI-239 and HBI-239-processed miRNA predicted good prognosis in angio-immunoblastic T-cell lymphoma (AITL) and PTCL not otherwise specified (PTCL-NOS) (86). Berquet et al investigated the snoRNA expression profiles in B-cell chronic lymphocytic leukemia (CLL) patients and identified that immunoglobulin heavy chain variable region gene (IGHV)-mutant patients exhibiting overexpression of 20 snoRNAs had a shorter treatment-free survival (TFS) (87). SNORA70F and SNORD116-118 were developed into a 2-snoRNA model that appeared to distinguish two different prognostic CLL groups (88).…”
Section: The Functions Of Snornasmentioning
confidence: 99%
“…Induction of C/D box snoRNAs has been reported to favor leukemogenesis 44 . A number of snoRNAs have been reported to predict the clinical outcome in early stage as well as IGHV mutated CLL 45,46 . Various tRNA fragments have been reported to induce transient translational arrest 42 and tRNA derived small RNAs can function similarly to miRs.…”
Section: Sr Nomentioning
confidence: 99%
“… 75 Furthermore, after CLL cells were induced to proliferate, 7 snoRNAs continued to be up-regulated with proliferation, while 2 snoRNAs (SNORA80 and SNORD1A) were down-regulated. 75 It is evident that snoRNAs are subject to complex regulation during the proliferation of CLL cells. Some snoRNAs may be deregulated during proliferation, whereas others may continue to be up-regulated, and the latter likely have important regulatory functions.…”
Section: Expression and Function Of Snornas In Leukemiamentioning
confidence: 94%